Mental health status of orphans and vulnerable children in residential institutions in a city in South-West Nigeria - Aladegboye, Mercy; Olowokere, Adekemi; Komolafe, Abiola; Ayamolowo, Sunday; Ogunlade, Bolarinwa; Adediran, Adeniyi (Adoption & fostering, 2025)
Background Mental health problems are a major cause of illness worldwide. They are common among children in low- and middle-income countries like Nigeria, with one in six young Nigerians reporting mental health issues. Aims This study assessed the mental health status of orphans and vulnerable children in residential institutions and the availability of mental health services. Methods A cross-sectional descriptive design was employed, and multi-stage sampling was used to select 384 orphans and vulnerable children from residential institutions. A pre-tested parents’ version of the Strengths and Difficulties Questionnaire (SDQ) and self-developed structured questions were used to collect the data. Results Results showed that 44.5% (n = 171) of children had scores that fell within the abnormal category in the total difficulty score on the SDQ. Mental health assessments before/during admission into the residential institution were available to 26.6% (n = 102) of orphans and vulnerable children. A significant association existed between mental health status and orphan status type of institution, age and duration of stay in the institution. The results further showed that being maternal orphans and living in government-owned residential institutions independently predicted abnormal difficulty scores. Conclusions This study underscores the need for mental health assessment and care among children in residential institutions. Plain language summary Mental health problems are a major cause of illness worldwide. This is more common among children and adolescents in low- and middle-income countries like Nigeria, with one in six young Nigerians reporting mental health problems, such as depression and anxiety. This study assessed the mental health of children residing in 12 children’s residential institutions and the availability of mental health services. Data were collected using a questionnaire. The results of the study showed that a significant proportion of the children who participated had scores that fell within the abnormal category in the total difficulty score of the Strengths and Difficulties Questionnaire (a tool used to assess children and young people’s mental health). Mental health assessments before or during admission into a residential institution were made available to fewer than half of the study participants. A significant association was found to exist between mental health status and orphan status, ownership of the residential institution and the duration of the child’s stay there. The results further showed that being a maternal orphan and living in a government-owned residential institution independently predicted an abnormal difficulty score. This study therefore underscores the need for mental health assessments and care for children in residential institutions.